2008
DOI: 10.1002/jrs.1909
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamical properties of glucose aqueous solutions by depolarized Rayleigh scattering

Abstract: Depolarized Rayleigh scattering (DRS) spectra of glucose aqueous solutions measured from 0.01 to 1000 cm −1 reveal the presence of two distinct relaxation processes, in addition to the intermolecular Raman modes of the water network. The slow relaxation process with a characteristic time of tens of picoseconds is due to the glucose rotational diffusion and is spectrally separated from the fast relaxation process at picosecond time scales commonly attributed to the hydrogen-bond lifetime; this latter time clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 28 publications
8
51
0
Order By: Relevance
“…In particular, we follow the effects of (a) temperature, (b) solute concentration, and (c) type of CD on the Raman bands commonly assigned to bending-like (B) and stretching-like (S) modes of tetrahedral H-bonded structures of liquid water (located at around 50 and 170 cm −1 , respectively), in order to extract information on the structural properties of water in the mixtures. The results will be discussed in terms of structural modification of the H-bond network of liquid water perturbed by the solute and compared with the behavior observed for glucose 29,33 as monomeric unit of CD, in order to give a qualitative synopsis of the properties of different systems. Finally, the effect of different size and of substitution of the OH groups of the glucose rings of the β-CD molecules on the B and S vibrational modes is also explored.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, we follow the effects of (a) temperature, (b) solute concentration, and (c) type of CD on the Raman bands commonly assigned to bending-like (B) and stretching-like (S) modes of tetrahedral H-bonded structures of liquid water (located at around 50 and 170 cm −1 , respectively), in order to extract information on the structural properties of water in the mixtures. The results will be discussed in terms of structural modification of the H-bond network of liquid water perturbed by the solute and compared with the behavior observed for glucose 29,33 as monomeric unit of CD, in order to give a qualitative synopsis of the properties of different systems. Finally, the effect of different size and of substitution of the OH groups of the glucose rings of the β-CD molecules on the B and S vibrational modes is also explored.…”
Section: Introductionmentioning
confidence: 97%
“…In this context, recently, depolarized light scattering has been used by some of us as a powerful tool to distinguish spectral features coming from solute rotational dynamics, hydrogen bonding solvent dynamics, and vibrational intermolecular modes of saccharides and proteins aqueous solutions (Rossi et al, submitted for publication). [28][29][30][31][32] Here, making use of low-frequency depolarized Raman spectra, we focus the attention on the vibrational properties of CD-water solutions. In fact, the ability of CD to form hydrogen bonds with water is expected to modify the regular network of water-water hydrogen bonds in the solvent molecules placed around the solute, and such changes should in principle influence the low-wavenumber vibrational spectrum of water.…”
Section: Introductionmentioning
confidence: 99%
“…From calculations of the dynamical susceptibility, the presence of bending-like and stretching-like modes of tetrahedal H-bonded structures of liquid water could be established. In another paper from the same laboratory, [191] depolarised Rayleigh www.interscience.wiley.com/journal/jrs scattering served to provide structural and dynamical properties of glucose aqueous solutions. A new insight on the hydrogen bonding structures of nanoconfined water (water adsorbed in nanoporous silica glass) was gained by Crupi et al [192] who performed a detailed study of the contour of the O-H stretching band of water in the bulk state and in a restricted geometry, as a function of temperature and the size of the geometrical confinement.…”
Section: Other Studies In Liquidsmentioning
confidence: 99%
“…Many studies revealed that the structure and kinetics of glucose aqueous solutions were affected due to strong hydrogen bonds, [7][8][9][10][11][12][13][14][15][16] including loss of the tetrahedral ordering typical of the bulk water, 7,8 two hydrates composition with the pentahydrate (C 6 H 12 O 6 ·5H 2 O) and the dihydrate (C 6 H 12 O 6 ·3H 2 O), 13 reduction in water translational and rotational mobility 7 and decrease of glucose translational diffusion coefficients. 16 Hydrogen bonding structure and kinetics of glucose aqueous solutions have been studied and it has been found that water and glucose clusters were formed by hydrogen bonds 17 and the hydrogen bond lifetime increased as glucose concentration increases.…”
Section: Introductionmentioning
confidence: 99%
“…16 Hydrogen bonding structure and kinetics of glucose aqueous solutions have been studied and it has been found that water and glucose clusters were formed by hydrogen bonds 17 and the hydrogen bond lifetime increased as glucose concentration increases. 14 There are five hydroxyl groups in a glucose molecule and hydrogen bonding abilities of these hydroxyl groups may be different. In fact, molecular dynamics simulation studies found that the hydroxyl groups were more efficient hydrogen bond donors than acceptors.…”
Section: Introductionmentioning
confidence: 99%